Estimating and costing in civil engineering: theory and practice; including specifications and valuations - Dutta, B.N (UBS Pub, 2002)
Estimating and costing in civil engineering: theory and practice; including specifications and valuations / Dutta, B.N.. -- Kolkata: UBS Pub., 2002 658.1552 D361e25 25th ed. No. of Copies : 1